Electrocardiography in people living at high altitude of Nepal - Aryal, Nirmal (Heart Asia, 2017)
OBJECTIVE: The main objective of this study was to estimate the prevalence of coronary heart disease (CHD) of high-altitude populations in Nepal determined by an ECG recordings and a medical history. METHODS: We carried out a cross-sectional survey of cardiovascular disease and risk factors among people living at four different altitude levels, all above 2800 m, in the Mustang and Humla districts of Nepal. 12-lead ECGs were recorded on 485 participants. ECG recordings were categorised as definitely abnormal, borderline or normal. RESULTS: No participant had Q waves to suggest past Q-wave infarction. Overall, 5.6% (95% CI 3.7 to 8.0) of participants gave a self-report of CHD. The prevalence of abnormal (or borderline abnormal) ECG was 19.6% (95% CI 16.1 to 23.4). The main abnormalities were: right axis deviation in 5.4% (95% CI 3.5 to 7.7) and left ventricular hypertrophy by voltage criteria in 3.5% (95% CI 2.0 to 5.5). ECG abnormalities were mainly on the left side of the heart for Mustang participants (Tibetan origin) and on the right side for Humla participants (Indo-Aryans). There was a moderate association between the probability of abnormal (or borderline abnormal) ECG and altitude when adjusted for potential confounding variables in a multivariate logistic model; with an OR for association per 1000 m elevation of altitude of 2.83 (95% CI 1.07 to 7.45), p=0.03. CONCLUSIONS: Electrocardiographic evidence suggests that although high-altitude populations do not have a high prevalence of CHD, abnormal ECG findings increase by altitude and risk pattern varies by ethnicity.